AN ERROR ANALYSIS OF STUDENTSâ GRAMMAR IN WRITING (A Mix Method at Darul Ulum, A Private Islamic Boarding Senior High School in Lhokseumawe) - Helmiyadi, Helmiyadi (STKIP Bina Bangsa Getsempena Banda Aceh, 2018)
AbstractThe aim of the research is to find out the grammar errors which are commonly made by the students of Darul Ulum Islamic Boarding Senior High School in their writing and to find out the causes of grammar errors which are commonly made by the students of Darul Ulum Islamic Boarding Senior High School in their writing. This research uses a qualitative and quantitative approach and its type is a mix study. The population is the total object of the research. In this research, the population was all the students of the first year students of MAS Darul Ulum in academic year 2015/2016, they are 120 students and divided into 56 male students and 64 female students. Result of the research from test most of the first year students of MAS Darul Ulum Lhokseumawe made many errors in grammatical aspects in writing, a high percentage of errors was found in one out of three categories. The highest error category was tense errors. They occurred 88 errors, while article is 19 time of errors and sentence 10 of errors. Total of all errors found in these three categories are 117 errors occurring in whole categories. Moreover, the students felt difficult in getting ideas to begin free writing. The causes of errors were made by the students because of lack of interactive facilities is one of the problems to develop interactive classroom activities. The errors made by students were influenced by their mother tongue, and were also caused by the difficulties of the students in learning the second language.Â Keywords: Error Analysis, Grammar, Writing